DETERMINANTS OF EARNINGS PERSISTENCE LITERACY STUDY MANUFACTURING IN INDONESIA - Menggalawati, Solechah Dwi; Hardiningsih, Pancawati (STIE Pelita Nusantara Semarang, 2024)
This research aims to analyze the impact of industry type, debt levels, and sales volatility on a company's ability to predict and maintain profits over time. Because profit persistence is the main determinant of the sustainability of a company's profitability and the quality of its financial reporting, this research is very important. The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2019 and 2022. Purposive sampling is the approach used for sampling, and a total of 23 companies or 83 observations for the sample were selected. Multiple linear regression analysis is the analysis method used. The research results show that company size, as a control variable, has a positive impact on earnings persistence, sales volatility has a negative impact, while debt level and industry type have a positive effect on earnings persistence. Overall, this research has significant consequences for decision making, financial statement analysis, and profit prediction for future periods.